Association of serum specific IgE levels with asthma in autumn pollen-induced allergic rhinitis: A retrospective analysis. (4th May 2019) - Cui, Le; Yin, Jia
ABSTRACT: Background : Artemisia and Humulus pollen are the two most important aeroallergens of autumn allergies in North China. Cross-sectional data in 2001 have shown that allergic rhinitis often preceded or occurred at the same time as asthma in patients with autumn pollinosis in North China. Objective : We used this cross-sectional data to investigate the association of serum specific IgE (sIgE) levels to Humulus and/or Artemisia pollen with the onset of asthma in patients with autumn pollen-induced allergic rhinitis. Methods : 1096 patients with autumn pollinosis were face-to-face interviewed and underwent sIgE tests to Artemisia and Humulus . The temporal sequence of allergic rhinitis and asthma was documented. 1013 patients were positive to Artemisia and/or Humulus by sIgE. Multinomial logistic regression and survival analysis were used to examine the potential implication of sIgE levels for the progression of asthma in autumn pollen-induced allergic rhinitis. Results : Of the 1013 participants with a positive sIgE test to Artemisia and/or Humulus, 563 (55.6%) had a history of allergic rhinitis which preceded or occurred at the same time as asthma. 450 (44.4%) had allergic rhinitis alone. After controlling of sex, age at onset of allergic rhinitis, and parental asthma, the risk of developing asthma increased with the levels of sIgE to both Artemisia and Humulus ( p < 0.05). In Kaplan–Meier analysis, IgE classes 5–6 to Humulus or Artemisia increased the risk of asthma development ( p < 0.05). Conclusion : Autumn pollen-induced allergic rhinitis often coexists with seasonal asthma. The incidence of asthma is more pronounced when the sIgE level was higher.